Sources of Risk and Related Effects in the Malaysian Construction Industry - Ting, Sim Nee; Beatrice, Jarit (Springer Nature, 2020)
Construction projects nowadays have higher complexities, calling for increased awareness, assessment and management of the risks involved. Key construction risks need to be identified, assessed and methods on risk mitigation need to be mapped out to better managed the potential of undesirables events within projects. The aim of the study was to provide a compilation of risk and its effects to be used as risk data for the Malaysian construction industry. Data was collected by conducting structured questionnaire surveys and distributing it to professionals involved in the construction industry. The overall discussion would focus on the sources of risk related to each specific group; the direct effects of these risks, and also the correlation between the sources and effects. It is hopeful that through this research, a proper knowledge or risk retention centre can ultimately be created to aid future effective qualitative and quantitative risk analysis for all construction projects.